Shared decision-making and client-reported dose satisfaction in a longitudinal cohort receiving injectable opioid agonist treatment (iOAT) - Scott Beaumont; Tianna Magel; Scott MacDonald; Scott Harrison; Martin Schechter; Eugenia Oviedo-Joekes (Substance Abuse Treatment, Prevention, and Policy, 2024)
Abstract Background Across different types of oral Opioid Agonist Treatment for people with Opioid Use Disorder, receiving a dose that meets their needs is associated with better outcomes. Evidence also shows patients are more likely to receive an “adequate dose” when their prescribers are involving them in decision making. Neither of these findings have been studied in the context of injectable Opioid Agonist Treatment, which is the purpose of this study. Methods This study was a retrospective analysis of an 18-month prospective longitudinal cohort study of 131 people receiving injectable Opioid Agonist Treatment. In the 18-month study, observations were collected every two months for one year, and then once more at 18 months. At 6 months, participants were asked whether their dose was satisfactory to them (outcome variable). Generalized Estimating Equations were used, to account for multiple observations from each participant. The final multivariate model was built using a stepwise approach. Results Five hundred forty-five participant-observations were included in the analysis. Participant-observations were grouped by “dose is satisfactory” and “wants higher dose”. From unadjusted analyses, participants were less likely to report being satisfied with their dose if they: were Indigenous, had worse psychological or physical health problems, had ever attempted suicide, were younger when they first injected any drug, were a current smoker, felt troubled by drug problems, gave their medication a lower “drug liking” score, and felt that their doctor was not including them in decisions the way they wanted to be. In the final multivariate model, all previously significant associations except for “current smoker” and “troubled by drug problems” were no longer significant after the addition of the “drug liking” score. Conclusions Patients in injectable Opioid Agonist Treatment who are not satisfied with their dose are more likely to: be troubled by drug problems, be a current smoker, and report liking their medication less than dose-satisfied patients. Prescribers’ practicing shared decision-making can help patients achieve dose-satisfaction and possibly alleviate troubles from drug problems. Additionally, receiving a satisfactory dose may be dependent on patients being able to access an opioid agonist medication (and formulation) that they like.